Determinan Volume Ekspor Tepung Kakao Indonesia - Christina, Elma (Universitas Udayana, 2025)
Cocoa is one of Indonesia’s leading agricultural commodities. The government’s downstream processing policy encourages increased exports of processed cocoa products, particularly cocoa powder, to reduce reliance on raw cocoa bean exports. This study aims to analyze the simultaneous and partial effects of the dollar exchange rate, trade openness index, export tax, and geographical distance on Indonesia’s cocoa powder export volume. The research employs panel data regression analysis. The results indicate that all four variables have a significant simultaneous effect on cocoa powder export volume. Partially, the exchange rate, trade openness index, and distance have a negative and significant effect, while the export tax has a positive and significant effect. These findings highlight the importance of strengthening downstream policies by regulating trade openness, imposing export taxes on raw materials, maintaining exchange rate stability, and improving logistics infrastructure to address geographic trade barriers.